Protomaster of the Frescoes in the Paracclesion of the Holy Anargyroi in the Vatopedi Monastery (1365/1366–1368) - Gavrilović, Anđela Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The original fresco of St. John Chrysostom in the central apse of the parecclesion of Holy Anargyroi in Vatopedi monastery on Holy Mount Athos, the foundation of Serbian Despot Jovan Uglješa (1365–1371), has been recently published in scholarly literature for the first time. In 1847, new frescoes were painted over all the original ones. In 1995, several original frescoes from the time of Despot Jovan Uglješa were cleaned and made visible, but only few of them have been published (Archangels Michael and Gabriel in the central apse). The recently published high-quality photograph of the original fresco of St. John Chrysostom in the central apse offers a comprehensive analysis, on the basis of which this fresco is, in the present paper, attributed to Serbian painter Metropolitan Jovan Zograf. In addition to the iconographic analysis, the handwriting of this artist provides definitive evidence of his authorship of the frescoes. It is demonstrated that the letters next to the figure of St. John Chrysostom in the parecclesion of Holy Anargyroi are identical to the letters next to the figure of the same saint in the Andreaš monastery. Furthermore, the palaeographic analysis and comparison of the texts written on the rolls of St. John Chrysostom in Holy Anargyroi (the Prayer of Offering) and of the same saint and of St. Peter of Alexandria in Andreaš leads to the same conclusion. In the same way, the study shows that Metropolitan Jovan Zograf also painted the representation of Christ Melismos on the Holy Table next to the figure of St. John Chrysostom and the figures of Archangels Michael and Gabriel worshipping the Mother of God in the register above the scene of Officiating of Church Fathers. On the same basis, it can be stated with certainty that Metropolitan Jovan Zograf also painted the original figure of St. Gregory the Theologian, which is still waiting to be uncovered from the new, 19th-century fresco layer. Finally, it can be concluded with certainty that Metropolitan Jovan Zograf, in the capacity of a protomaster, painted the original 14th-century ktetor’s composition featuring Serbian Despot Jovan Uglješa Mrnjavčević with the model of the parecclesion in his left hand (repainted in 1847). Several facts support this conclusion. The Greek painter, Matthew, who repainted the parecclesion frescoes in the 19th century repeated the appearance and gestures of the original 14th-century frescoes. Consequently, he also repeated the appearance of Serbian Despot Jovan Uglješa, leaving the original fresco below his own new layer intact (as is the case with the already mentioned original frescoes in the central apse which have been entirely preserved under the new 19th-century fresco layer). The conclusion that the original fresco depicting Serbian ktetor is still preserved can be further proven by the comparison of the existing portraits of Despot Jovan Uglješa: the repainted fresco in the narthex of the parecclesion of Holy Anargyroi and the original, posthumous portrait preserved partially in the narthex of the Monastery of St. John Prodromos on Mount Menoikeion, executed shortly after his death in 1371. Both the repainted portrait from the Monastery of Vatopedi and the posthumous portrait of Serbian Despot in the Monastery on Mount Menoikeion faithfully illustrate his portrait traits, showing strong similarity with the portrait traits of his elder brother Vukašin Mrnjavčević in Psača Monastery. The portrait of Despot Jovan Uglješa in the parecclecion of Holy Anargyroi was executed during the co-rulership of Serbian Tsar Stefan Uroš V (1355–1371) and King Vukašin (1365–1371). It was the time of great flourishing of Holy Mount Athos, which was under the Serbian rule and under the protectorate of the Nemanjić and Mrnjavčević dynasties. Despite the limited number of frescoes painted by Metropolitan Jovan Zograf in the parecclesion of Holy Monastery of Vatopedi, they have the highest artistic value, as they enhance our understanding of the era in which he worked, demonstrating that he had already established himself as a highly skilled painter by the beginning of the latter half of the 1360s. The paper offers a more precise dating of the frescoes of the pareclession: the original donor’s composition representing Despot Jovan Uglješa, is dated to 1365/1366, as it was created first, whereas the frescoes located in the bema of the central apse, which were painted immediately afterward, are dated to 1366–1368.